Group delay time and Hartman effect in strained Weyl semimetals. (21st October 2019) - Xu, Zhonghui; Siu, Zhuo Bin; Chen, Yan; Huang, Jinsong; Li, Yanling; Sun, Chi; Yesilyurt, Can; Jalil, Mansoor B A
Abstract: The group delay time was theoretically studied in Weyl semimetals (WSMs) in the presence of strain. The Hartman effect, where the delay time for tunneling through a barrier tends to a constant for large barrier thickness, can be observed in WSMs when the incident angles and, and the unidirectional strain tensor u 33 and shear strain tensor u 32, are larger than some critical values. We show that the Hartman effect is strongly dependent on the strength of the unidirectional strain tensor u 33 and the ratio of the shear strain tensor . We also found that tensile and compressive strains have different effects on the group delay time and the transmission probability T in WSMs. Our study shows the possibility of modulating the group delay time and the Hartman effect in strained WSMs.